Consumers' Perceptions of Healthy Food Availability in Online Food Delivery Applications (OFD Apps) and Its Association With Food Choices Among Public University Students in Malaysia - Eu, Elisa Zhen Rong; Sameeha, Mohd Jamil (Frontiers in Nutrition, 2021)
This retrospective cross-sectional study was conducted to study consumers' perceptions of healthy food availability in online food delivery applications (OFD apps) among public university students in Malaysia and its association with their food choices. A total of 290 subjects aged 19–29 years old were recruited from 20 public universities in Malaysia via snowball sampling. Data was collected through an online questionnaire which consisted of socio-demographic status, use of OFD apps (most frequently used brand, usage frequency, food choice, and expenditure per transaction), factors affecting food choice in OFD apps, consumers' perceptions of healthy food availability in OFD apps and recommendation for improvements. The most frequently used apps among the subjects was Food Panda (46.6%), however, majority of the subjects in this study (41.4%) rarely used OFD apps. Also, most of the subjects ordered unhealthy food (77.6%) and spent up to RM15–RM19 for each transaction (43.1%). There was no significant difference between the use of OFD apps and gender (p > 0.05). Among the five food choice motives, “price and convenience” motive was the most influencing food choice factor in OFD apps. Majority of the subjects (76.9%) had a negative perception of healthy food availability (variety, price, and quality of healthy food) in OFD apps. No significant association was found between consumers' perceptions of healthy food availability in OFD apps and their food choices made in OFD apps among the subjects in this study (p > 0.05). Also, majority (85.9%) responded they are keen to purchase healthy foods through OFD apps if they are given an option. However, most Malaysian public university students perceived that there were not much variety of healthy food, of good quality and affordable price, available in OFD apps. This finding suggests that the online food environment in Malaysia are perceived as unhealthy. Future studies can explore the online food environment particularly its impact on community health and well-being. Public health professionals and policymakers need to address the online food environment issues as part of the obesogenic food environment in Malaysia especially when OFD is one of the most convenient service in this country.